Routledge handbook of international organization - Reinalda, Bob (Routledge, 2019)
This handbook brings together scholars whose essays discuss significant issues with regard to international organization as a process and international organizations as institutions. Although the focus is on intergovernmental organizations (IGOs), non-governmental organizations (NGOs) are discussed where relevant. The handbook is divided into six parts: Documentation, data sets and sources, International secretariats as bureaucracies, Actors within international bureaucracies, Processes within international bureaucracies, Challenges to international organizations, and Expanding international architectures. The state-of-the-art articles are meant to encourage current and future generations of scholars to enjoy working in and further exploiting the field and are also of great interest to practitioners of international organization and global governance.